Chefs d'oeuvres des collections suisses de Manet à Picasso. - Huggler, Max (Lausanne : Palais de Beaulieu, 1964)
Boccioni, Umberto ; Bonnard, Pierre ; Boudin, Eugène ; Bourdelle, Antoine ; Brancusi, Constantin ; Braque, Georges ; Cézanne, Paul ; Chagall, Marc ; De Chirico, Giorgio ; Corinth, Lovis ; Cross, Henry-Edmond ; Degas, Edgar ; Derain, André ; Despiau, Charles ; van Dongen, Kees ; Duchamp-Villon, Raymond ; Dufy, Raoul ; Dunoyer de Segonzac, André ; Ensor, James ; Friesz, Othon ; Gauguin, Paul ; van Gogh, Vincent ; Gris, Juan ; Hofer, Carl ; Jawlensky, Alexej von ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Klee, Paul ; Kokoschka, Oskar ; Laurens, Henri ; Leger, Fernand ; Liebermann, Max ; Luce, Maximilien ; Macke, August ; Maillol, Aristide ; Manet, Edouard ; Manguin, Henry ; Marc, Franz ; Marini, Marino ; Marquet, Albert ; Matisse, Henri ; Miro, Joan ; Modigliani, Amedeo ; Mondriaan, Piet ; Monet, Claude ; Moore, Henry ; Morandi, Giorgio ; Morisot, Berthe ; Munch, Edvard ; Nicholson, Ben ; Nolde, Emil ; Pechstein, Max ; Picasso, Pablo ; Pissarro, Camille ; Redon, Odilon ; Renoir, Auguste ; Rodin, Auguste ; Rouault, Georges ; Rousseau, Henri ; Schmidt-Rottluff, Karl ; Seurat, Georges ; Signac, Paul ; Sisley, Alfred ; Soutine, Chaim ; de Staël, Nicolas ; de Toulouse-Lautrec, Henri ; Utrillo, Maurice ; Vallotton, Félix ; Valtat, Louis ; de Vlaminck, Maurice ; Vuillard, Edouard ; Wols, Otto
bibliografie
biografie
Frans
boek
Keywords: Zwitserland